Genomic approaches for cross-species extrapolation in toxicology : proceedings from the Workshop on Emerging Molecular and Computational Approaches for Cross-Species Extrapolations, 18-22 July 2004, Portland, Oregon, USA /: proceedings from the Workshop on Emerging Molecular and Computational Approaches for Cross-Species Extrapolations, 18-22 July 2004, Portland, Oregon, USA. (©2007) - Unknown
No abstract available